2010
DOI: 10.5125/jkaoms.2010.36.5.380
|View full text |Cite
|
Sign up to set email alerts
|

Donor site morbidity of anterior iliac crest for reconstruction of the jaw

Abstract: (J Korean Assoc Oral Maxillofac Surg 2010;36:380-4) Ⅰ. 서 론 Daegu,[700][701][702][703][704][705] The iliac crest has been the accepted place to obtain bone for reconstruction in oral and maxillofacial surgery. The iliac crest has many advantages because of its accessibility, large amount of cancellous bone, relative ease of bone harvest, possibility of two team approach and ability to close the wound primarily. This study evaluated retrospectively the morbidity of bone harvesting from the anterior iliac cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Other factors may include 'rigid' immobilization of the graft on a reconstruction plate, prophylactic antibiotic administration, extended postoperative antibiotic use and probably the benign nature of the lesions in most of our subjects. Lee et al 17 corroborated our findings in their retrospective review of donor-site morbidity of anterior iliac crest for reconstruction of the jaw, and concluded that split-thickness bone harvest from the inner table of the anterior iliac crest is a well-accepted procedure with relatively low morbidity. Lee et al 17 , however, retained the outer split portion of the iliac crest in situ (only using the inner half for mandibular reconstruction), while both inner and outer halves were utilized in our study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Other factors may include 'rigid' immobilization of the graft on a reconstruction plate, prophylactic antibiotic administration, extended postoperative antibiotic use and probably the benign nature of the lesions in most of our subjects. Lee et al 17 corroborated our findings in their retrospective review of donor-site morbidity of anterior iliac crest for reconstruction of the jaw, and concluded that split-thickness bone harvest from the inner table of the anterior iliac crest is a well-accepted procedure with relatively low morbidity. Lee et al 17 , however, retained the outer split portion of the iliac crest in situ (only using the inner half for mandibular reconstruction), while both inner and outer halves were utilized in our study.…”
Section: Discussionsupporting
confidence: 85%
“…This ultimately reduces donor site morbidity. A 'split iliac crest bone graft' has been described by Lee et al 17 for mandibular reconstruction. The length of the defect created following ablation in our study ranged from 4 to 12 cm.…”
Section: Discussionmentioning
confidence: 99%